Theoretical study of the initial stage of InN growth on cubic zirconia (111) substrates. Issue 3 (14th December 2012) - Guo, Yao; Inoue, Shigeru; Kobayashi, Atsushi; Ohta, Jitsuo; Fujioka, Hiroshi
Abstract An initial stage of InN growth on cubic zirconia (111) substrates has been investigated using first‐principles calculations based on density functional theory (DFT). We have evaluated adsorption energies of indium and nitrogen atoms on cubic zirconia (111) surfaces, and have found that the differences in the adsorption energies of the indium atoms at various adsorption sites were small, indicating that the migration of the indium atoms on zirconia (111) surfaces occurs readily. On the other hand, we have found that the differences in the adsorption energies of the nitrogen atoms at various adsorption sites were large, implying that the nitrogen atoms tend to stay at the stable site with the largest adsorption energy, which was identified as the O–Zr bridge site. These results suggest that the first layer of InN films is the nitrogen layer. In addition, we have found that the energetically favorable arrangement is comprised of InN(0001)//cubic zirconia (111) and InN <![CDATA[$ [11\bar 20] $]]> <inline-graphic xlink:href="ark:/27927/pgg1v86687q" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />//cubic zirconia <![CDATA[$ [1 \bar 10], $]]> <inline-graphic xlink:href="ark:/27927/pgg1v866865" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> which is quite consistent with previously obtained experimental data. Furthermore, the hybridization effect between N 2p and O 2p plays a crucial role in determining the interface structure for the growth of InN on cubic zirconia (111) surfaces. (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)